Childhood, adulthood, and cumulative traumatic events experienced from childhood to adulthood and dementia risk: a population-based cohort study. - Xie, Ziwei; Li, Meiling; Sun, Huizi; Zhou, Chunmiao; Fu, Chunying; Wang, Qi; Dong, Caiyun; Hao, Wenting; Zhen, Xuemei; Zhu, Dongshan (Journal of Public Health: From Theory to Practice (2198-1833), 2025)
Aim: We aim to examine the association of traumatic events experienced in childhood, adulthood, and cumulative traumatic events experienced from childhood to adulthood, with the risk of all-cause dementia, including Alzheimer's disease (AD) and vascular dementia (VD), while considering the roles of sex. Subject and methods: We used data from the UK Biobank cohort study and 145,558 participants were included. Frequency of traumatic events (including emotional abuse, physical abuse, and sexual abuse) experienced in childhood and adulthood were collected. Cumulative number and type of traumatic events experienced from childhood to adulthood were also calculated. We used Cox proportional hazards models to estimate hazard ratios (HRs) and 95% confidence intervals (CI) for the association between traumatic events and risk of all-cause dementia. Sex-specific associations were also analyzed. Results: Compared to people who did not experience traumatic events in their life course, those who often experienced emotional, physical, and sexual abuse in childhood were associated with a higher risk of all-cause dementia, with HRs (95% CI) of 2.23 (1.34, 3.71), 3.16 (1.81, 5.53), and 3.23 (1.52, 6.89), respectively. Corresponding HRs (95% CI) in people who experienced traumatic events in adulthood were 1.42 (1.11, 1.82), 1.96 (0.97, 3.98), and 3.13 (1.18, 8.27), respectively. After cumulative type of traumatic events were calculated from childhood to adulthood, we found that people who experienced both emotional and physical abuse in childhood had the highest risk of all-cause dementia in later life with HRs (95% CI) of 1.94 (1.00–3.78). Conclusion: Traumatic events experienced in both childhood and adulthood were related to an increased risk of dementia. People who experienced both emotional and physical abuse in childhood had the highest risk of all-cause dementia.